2014
DOI: 10.3390/su6117850
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Expansion of China’s Urban Land Area: Evidence from Administrative Data and Night Lights, 1993–2012

Abstract: Abstract:The relationship between economic growth, expansion of urban land area and the broader issue of cultivated land conversion in China has been closely examined for the late 1980s and 1990s. Much less is known about recent urban expansion and if the effects of economic growth on this expansion have changed over time. This paper updates estimates of urban expansion for China and examines the relationship with city economic growth for 1993-2012. To see if patterns are robust to different types of evidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Night light remote sensing has been widely used in many fields including socioeconomic parameter estimation [34][35][36], urbanization evaluation [37,38], fishing boat mapping [39], land cover mapping [40][41][42][43], and humanitarian disaster evaluation [44][45][46]. This technique provides an opportunity to map spatial distribution of GDP [47,48], energy consumption [49,50], and public services [51,52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Night light remote sensing has been widely used in many fields including socioeconomic parameter estimation [34][35][36], urbanization evaluation [37,38], fishing boat mapping [39], land cover mapping [40][41][42][43], and humanitarian disaster evaluation [44][45][46]. This technique provides an opportunity to map spatial distribution of GDP [47,48], energy consumption [49,50], and public services [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this approach, Gibson and his colleagues found that the annual expansion rate of China's lit area in 287 prefectural cities during 1993-2012 is 8%, which is higher than 5% from official statistical yearbooks [37]. Yi and his colleagues proposed an Urban Light Index (ULI) to evaluate the urbanization process in 34 prefectural cities in Northeast China.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the GDP per capita increased from 1.96 × 10 4 RMB (2007) to 5.66 × 10 4 RMB (2014). The effect of rising GDP per capita and better services is to attract more rural people to migrate to the city, bringing more tourists and workers to Lhasa [29,31]. To simultaneously meet the economic development, population concentration, and old-city protection demands, the local government further implemented the "Lhasa City Master Plan 2009-2020" in 2009.…”
Section: Determinants For Lhasa Expansionmentioning
confidence: 99%
“…Note there is no single optical VANUI threshold for all urban clusters, which is usually higher for large urban clusters and lower for small urban clusters. A high threshold would have excluded too many small cities, but a low threshold would have led to implausibly large super-urban objects around big cities [3,32]. The threshold of 0.18 was based on medium urban clusters in the study area and, thus, may have missed some potential urban areas around small urban clusters.…”
Section: Super-urban Objectsmentioning
confidence: 99%
“…Though relatively small in area, the extent and change that urbanized lands have on socioeconomic and ecosystem functions, including human health and well-being, climate (e.g., urban heat island), water conservation (e.g., rainfall), air pollution (e.g., PM 2.5 ), biodiversity, ecosystem productivity and carbon cycling [1][2][3][4][5][6][7][8][9], are disproportionate at multiple scales. It has been increasingly recognized that urbanization needs to be considered as a necessary component of studying regional and global change [10].…”
Section: Introductionmentioning
confidence: 99%